A study on differentiation of depiction between scatterer and reflector to assist epidural anesthesia by ultrasound. (28th April 2021) - Hashimoto, Takumi; Mori, Shohei; Arakawa, Mototaka; Onishi, Eiko; Yamauchi, Masanori; Kanai, Hiroshi
Abstract: A sharp depiction of the puncture point of the needle by differentiating muscle and bone is required for ultrasound-guided epidural anesthesia in the thoracic spine. In the present paper, we proposed a method for depicting the thoracic vertebral surface by utilizing the difference between scattering and reflection characteristics. This method estimates whether an object is a scatterer or a reflector referring to the scattering and reflection characteristics acquired in the water tank experiment. The proposed method was applied to basic experiments and in vivo experiments. In the basic experiments, the matching using root mean squared error allowed us to differentiate the depiction between scattering and reflection. In the in vivo experiment, we were able to estimate the position of the bone as a reflector and the slope was generally correct.